2020
DOI: 10.31729/jnma.5230
|View full text |Cite
|
Sign up to set email alerts
|

Sacrococcygeal Teratoma: A Case Report

Abstract: Sacrococcygeal teratoma is rare and happens in 1:35,000 to 40,000 live births. It is more common in girls than boys with the reported ratio of 3:1 to 4:1. We herein report an unusual case of a huge sacrococcygeal teratoma, which was more than half of the size and weight of the baby which was terminated at 24 weeks of gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Sacrococcygeal teratoma is a tumour that develops in the sacrococcygeal area that incorporate tissue from many primitive germ layers. [6] Its cause remains unknown [7] The classification of SCT according to AAPSS American Academy of pediatrics surgical section (AAPSS) in 1973 described as follows.…”
Section: Discussionmentioning
confidence: 99%
“…Sacrococcygeal teratoma is a tumour that develops in the sacrococcygeal area that incorporate tissue from many primitive germ layers. [6] Its cause remains unknown [7] The classification of SCT according to AAPSS American Academy of pediatrics surgical section (AAPSS) in 1973 described as follows.…”
Section: Discussionmentioning
confidence: 99%
“…[94] The CO, PM 2.5 (mass), PM2.5 (number), PM 10 (mass), and PM 10 (number) emission factors developed over here were varying in the range of 110-120 mg g −1 of incense, 2.5-3 mg g −1 of incense, 800-1100 #particle/μg of incense, 32-33 mg g −1 of incense, 1200-1400 particle/μg of incense respectively. [18,26,[95][96][97][98] A team led by Bala highlighted the effect of PMs under closed and open ventilation conditions where the investigators found a higher percentage (8-10 times) of PM 10 in the closed-ventilated conditions during the burning of incense. [99] A team led by Gupta also performed similar activities where the investigators tried to eliminate the PMs and other components from an open and closed system by using an indigenous air purifier.…”
Section: Health Risks Associated With Particulate Matter and Their As...mentioning
confidence: 99%
“…The toxic components of incense smoke including particulate matter aggravate the chronic COPD risk among the respiratory affected patients. [23,26] Multiple studies across the globe have raised concerns about the enhanced risk of COPD and related cardiac disorders among women who regularly burns incense sticks in their homes. [133,134] COPD is a coronary lung disease normally observed in cigarette smokers.…”
Section: Effect Of Pm 25 On Chronic Respiratory Disordermentioning
confidence: 99%
See 2 more Smart Citations